Trajectories of BMI Before Diagnosis of Type 2 Diabetes: The Rotterdam Study. Issue 6 (7th May 2020) - Nano, Jana; Dhana, Klodian; Asllanaj, Eralda; Sijbrands, Eric; Ikram, M. Arfan; Dehghan, Abbas; Muka, Taulant; Franco, Oscar H.
Abstract : Objective: People with diabetes show great variability in weight gain and duration of obesity at the time of diagnosis. BMI trajectories and other cardiometabolic risk factors prior to type 2 diabetes were investigated. Methods: A total of 6, 223 participants from the Rotterdam Study cohort were included. BMI patterns before diagnosis of diabetes were identified through latent class trajectories. Results: During a mean follow‐up of 13.7 years, 565 participants developed type 2 diabetes. Three distinct trajectories of BMI were identified, including the "progressive overweight" group ( n = 481, 85.1%), "progressive weight loss" group ( n = 59, 10.4%), and "persistently high BMI" group ( n = 25, 4.4%). The majority, the progressive overweight group, was characterized by a steady increase of BMI in the overweight range 10 years before diabetes diagnosis. The progressive weight loss group had fluctuations of glucose and marked beta cell function loss. The persistently high BMI group was characterized by a slight increase in insulin levels and sharp increase of insulin resistance accompanied by a rapid decrease of beta cell function. Conclusions: Heterogeneity of BMI changes prior to type 2 diabetes was found in a middle‐aged and elderly white population. Prevention strategies should be tailored rather than focusing only on high‐risk individuals.